Educators' and Visitors' Perceptions of Invasive Species Education in Zoos. - Steele, Zachary T.; Pienaar, Elizabeth F. (Visitor Studies)
Management of invasive alien species (IAS) depends on public awareness and cooperation, which may be increased by effective IAS education by zoos. We administered a questionnaire to visitors (n = 221) and educators (n = 44) at three Association of Zoos and Aquariums facilities in Florida to explore their perceptions of the content and effectiveness of IAS education at these facilities. Most visitors recalled seeing IAS on display, with 80% of visitors stating that they considered zoos to be a place to learn about IAS. Both visitors and educators agreed that minimal information on how IAS are introduced to Florida was presented. They also agreed that greater implementation of shows and presentations pertaining to IAS would be highly effective in educating the public about IAS and the need for actions to mitigate species invasions. Zoos may improve their educational effectiveness by making visitors aware of IAS citizen science programs and implementing interactive educational methods.